Menentukan Rute Pengiriman Produk PT. Unicharm Indonesia Dengan Meminimalkan Biaya Transportasi Menggunakan Metode Saving Matrix di “CV. Jaya Abadi” - Dikdik Dermawan (Peneliti.net, 2022)
Transportation problems are an important aspect of everyday life. Transportation is also a very important component in the logistics management of a company. The process of distributing goods is one example. The product distribution route of PT. Unicharm Indonesia started from the CV warehouse. Jaya Abadi to the destination area has so far been less than optimal because in determining the route at this time the company does not have a special method used in determining the route, it only uses an estimate of the distance by looking at the number of requests without considering the vehicle capacity and distance from the warehouse to the destination, so it will affect the number of vehicle use can result in high transportation costs. This study aims to determine the optimal route and determine the minimum distribution cost savings. Product distribution of PT. Unicharm Indonesia conducted by CV. Jaya Abadi covers 2 provinces, namely Central Java Province and East Java Province. For distribution, use a fullbox truck with a capacity of 1,300 cartons. The data used are the distance between warehouses and agents and the distance between agents, the number of requests for each agent, and vehicle capacity. Data processing for determining the shortest route used the Saving Matrix method and for route sequencing the Nearest Insert and Nearest Neighbor methods were used. The results of the calculation in Central Java Province that resulted in a mileage of 3,086.3 Km there was a saving of 16.61%, a travel time of 4,629.55 minutes a saving of 8.92%, and a vehicle operating cost of Rp. 4,073,267,- 21.6% savings. East Java Province, which resulted in a mileage of 4,457.3 Km saving 25%, travel time 6,625.9 minutes, saving 0.6%, and vehicle operating costs Rp.3.739.744 saving 46.1%.